A new species of the alpheid shrimp genus Athanas Leach, 1814 (Decapoda: Caridea) from the Sea of Japan - Komai, Tomoyuki; Henmi, Yumi (Zootaxa, 2023)
A new species of the alpheid shrimp genus Athanas Leach, 1814 is described based on a holotype from Wakasa Bay, Sea of Japan side of Honshu, Japan, at a depth of 90 m. Athanas exilis n. sp. appears close to A. sydnyensis Anker & Ahyong, 2007, but is distinguished from the latter by some morphological features, including the different shape of the telson, the shorter antennular stylocerite, more strongly produced distal lamella of the antennal scaphocerite, and less developed armature of the merus of the major cheliped. Preliminary genetic analysis using the mitochondrial 16S rRNA gene was performed to compare interspecific genetic divergence within the genus.